Characterization and reduction of gradient-induced eddy currents in the RF shield of a TEM resonator. - Alecci, M; Jezzard, P (2002)
Radiofrequency (RF) shields that surround MRI transmit/receive coils should provide effective RF screening, without introducing unwanted eddy currents induced by gradient switching. Results are presented from a detailed examination of an effective RF shield design for a prototype transverse electromagnetic (TEM) resonator suitable for use at 3 Tesla. It was found that effective RF shielding and low eddy current sensitivity could be achieved by axial segmentation (gap width = 2.4 mm) of a relatively thick (35 microm) copper shield, etched on a kapton polyimide substrate. This design has two main advantages: first, it makes the TEM less sensitive to the external environment and RF interference; and second, it makes the RF shield mechanically robust and easy to handle and assemble.